Programmable thermocapillary shaping of thin liquid films. (23rd August 2022) - Eshel, Ran; Frumkin, Valeri; Nice, Matan; Luria, Omer; Ferdman, Boris; Opatovski, Nadav; Gommed, Khaled; Shusteff, Maxim; Shechtman, Yoav; Bercovici, Moran
Abstract: Abstract : We present a method that leverages projected light patterns as a mechanism for freeform deformation of a thin liquid film via the thermocapillary effect. We developed a closed-form solution for the inverse problem of the thin-film evolution equation, allowing us to obtain the projection pattern required in order to achieve a desired topography. We experimentally implement the method using a computer controlled light projector, which illuminates any desired pattern onto the bottom of a fluidic chamber patterned with heat–absorbing metal pads. The resulting heat map induces surface tension gradients in the liquid–air interface, giving rise to thermocapillary flow that deforms the liquid surface. If a polymer is used for the liquid film, it can then be photocured to yield a solid device. Based on the inverse-problem solutions and using this system, we demonstrate the fabrication of several diffractive optical elements, including phase masks for extended depth of field imaging, and for three-dimensional localization microscopy. The entire process, from projection to solidification, is completed in less than five minutes, and yields a sub-nanometric surface quality without any post-processing.